A high compression and resilience sheath-core composite fiber and preparation method thereof

By using step-by-step esterification and copolycondensation methods in ES fibers to prepare polyester copolyester as the leather core layer, the problem of thermodynamic incompatibility between the leather and core layer is solved, and the strength and compression resilience of the fiber are improved. It is suitable for composite fibers produced by hot air molding.

CN119121452BActive Publication Date: 2025-03-21JIANGSU JIANGNAN HIGH POLYMER FIBER
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411376795.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-03-21
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing ES fibers are thermodynamic incompatible with the core layer, prone to cracking, insufficient compression elasticity when used in warm filling materials, etc.

Method used

The copolyester with three segment structures was prepared as the skin layer by step esterification and copolycondensation method, and the copolyester with two segment structures was prepared as the core layer by coesterification and copolycondensation method. The composite fibers with excellent compression rebound rate were prepared by the skin-core composite spinning technology.

Benefits of technology

It solves the problem of fiber cracking, improves the strength and compression resilience of composite fibers, is suitable for hot air molding and processing, and is widely used in diapers, sanitary napkins and other products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005068880120000091
    Figure BDA0005068880120000091
  • Figure BDA0005068880120000092
    Figure BDA0005068880120000092
Patent Text Reader

Abstract

The present invention provides a high compression rebound sheath-core composite fiber and a preparation method thereof, which relates to synthesizing a new type of copolyester and then using a sheath-core composite spinning method to prepare a composite fiber with excellent compression rebound rate. A step-by-step esterification method and a copolycondensation method are used to prepare a copolyester A with three chain segment structures as the sheath layer, and the melting point is 125-140°C; a copolyester B with two chain segment structures is prepared by a coesterification and copolycondensation method as the core layer, and the core layer and the sheath layer have equivalent fluidity at the same temperature, and the melt index is 20-30g / 10min. The composite fiber with excellent compression rebound rate is prepared by sheath-core composite spinning, and the fiber mechanical strength is ≥2.5cN / dtex, the compression rebound rate is ≥85%, it is soft, skin-friendly and comfortable, and anti-cracking, etc. It can meet the requirements of hot air process molding and processing, and is widely used in diapers, sanitary napkins and other products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of development of functional polyester fiber products, and relates to a high compression-rebound sheath-core composite fiber and a preparation method thereof. Specifically, a polyester raw material specially used for composite spinning is synthesized and then composite spinning is performed to obtain a composite fiber with excellent mechanical properties and compression rebound. The sheath is a low-melting-point component, which can meet the requirements of hot air molding processing technology, greatly improving the quality of disposable sanitary products such as sanitary napkins, diapers, and panty liners. Background Art

[0002] ES fiber is the abbreviation of "Ethylene-Propylene Side By Side" in English. It is a kind of eye-catching polyolefin fiber developed by Chisso Corporation of Japan. ES fiber is made of two slices with different low melting points through a twin-screw spinning machine and a composite spinning method, that is, a low-melting point two-component composite fiber. ES fiber has the advantages of breathability and odor absorption, and is widely used in high-end sanitary napkins, diapers, medical masks and other sanitary products.

[0003] Chinese invention patent CN118308804A discloses a cool composite fiber and a preparation method thereof, and a skin-core composite fiber. The raw materials of the cool composite fiber are modified HDPE and modified PET. The modified HDPE contains modified cool powder, and the modified PET contains modified molybdenum disulfide. The cool composite fiber made of modified HDPE and modified PET has both high strength and high thermal conductivity. After combined use, the cool composite fiber can block the influence of environmental factors such as photoelectric heat on the cool feeling, and significantly improve the cool feeling of the cool composite fiber. Chinese invention patent CN118007274A provides an ES fiber containing wormwood active ingredients and its application in sweat-absorbing patches, wherein the core layer is composed of polypropylene, high-density polyethylene, super absorbent resin, nano-silicon dioxide, carbon nanotubes, wormwood extract and processing aids; the skin layer is composed of polyethylene, super absorbent resin, nano-silicon dioxide, modified coconut shell activated carbon, wormwood extract and processing aids; the ES fiber prepared by the invention can effectively inhibit bacterial growth and odor generation, and has excellent moisture absorption and antibacterial properties. Chinese invention patent CN116695280A discloses a three-dimensional spiral structure elastic ES fiber, wherein the shape of the fiber cross section of the ES fiber corresponding to the modified PP is a semi-cross shape, and the shape of the fiber cross section of the ES fiber corresponding to the PE is a zigzag shape; the three-dimensional spiral structure elastic ES fiber prepared by the invention not only overcomes the shortcomings of the existing ES fiber such as poor bulkiness, high weight due to high material density, and poor moisture absorption and moisture conduction function, but also has high self-curling properties. Chinese invention patent CN114875518A discloses an antibacterial ES fiber for a cool non-woven fabric and a preparation method thereof, which comprises taking ultrafine diatomaceous earth and stearic acid, stirring evenly, adding polypropylene, phosphite antioxidants, and PE wax, stirring evenly, and obtaining a core layer mixture; taking ultrafine diatomaceous earth and stearic acid, stirring evenly, adding polyethylene, phosphite antioxidants, and PE wax, stirring evenly, and obtaining a skin layer mixture; stirring the core layer mixture and the skin layer mixture evenly, extruding, spinning, stretching, drying, and cutting to obtain ES fibers, and soaking the ES fibers in a heat-conductive antibacterial solution for 50 minutes, taking them out, and drying them to obtain an antibacterial ES fiber for a cool non-woven fabric; the antibacterial solution is composed of ZnO-MOFs grafted with L-arginine and boron nitride grafted with Schiff base, which gives the ES fiber fabric good antibacterial and thermal conductivity, can quickly take away heat energy, and can be applied to cool antibacterial non-woven fabrics.

[0004] It can be seen from the above disclosed technology that the material surrounding the cortex is a polyolefin type, which is currently being functionally modified through blending, and then the performance is improved through the regulation of the composite spinning process.

[0005] Chinese invention patent CN118390199A provides a modified PBT-PET sheath-core composite fiber and a preparation method thereof, wherein the composite fiber has modified PBT as the sheath and PET as the core material; the modified PBT is prepared by using terephthalic acid and butene glycol as polymerization monomers and alkoxyphenylboronic acid as the third polymerization monomer; the modified PBT is used as the sheath, and a specific nitrogen-containing additive 2,2'-dipyrrolylmethane is added; it greatly improves the flame retardancy of the composite fiber and its stability at high temperatures. Chinese invention patent CN118308805A discloses a preparation method of a multifunctional wear-resistant PET sheath-core composite fiber, wherein terephthalic acid, ethylene glycol, and modified graphene oxide are used as raw materials to react under catalyst conditions to prepare the sheath PET, and the sheath PET and the core PET are melt-spun to prepare the multifunctional wear-resistant PET sheath-core composite fiber, wherein the surface friction coefficient of the sheath PET of the multifunctional wear-resistant PET sheath-core composite fiber is significantly reduced, and the lubricity of the sheath PET is significantly improved. Chinese invention patent CN118326557A discloses a modified hydrophobic PET core-skin composite fiber and a preparation method thereof. The modified hydrophobic PET core-skin composite fiber comprises a polyester core layer and a hydrophobic modified skin layer wrapped around the polyester core layer; of the polyester core layer and the hydrophobic modified skin layer, only the hydrophobic modified skin layer contains hydrophobic modified PET formed by copolymerization of a silane hydrophobic modifier, terephthalic acid and ethylene glycol; the silane hydrophobic modifier contains at least two alkoxy groups connected to silicon atoms; the invention introduces the silane hydrophobic modifier into the PET molecular chain by copolymerization, and adds it to the skin layer, and cooperates with the polyester core layer, so that the fiber has better hydrophobic performance and hydrophobic durability, and avoids a significant decrease in fiber strength caused by the introduction of the silane hydrophobic modifier. Chinese invention patent CN104532399A provides a colored polyethylene naphthalate (PEN) / polyethylene terephthalate (PET) concentric sheath-core composite fiber, wherein the sheath component includes a colored masterbatch and PEN in a weight ratio of 5-15:95-85, and the colored masterbatch includes a colored powder and PEN in a weight ratio of 25-35:75-65; and the core component includes PET; wherein the weight ratio of the sheath component to the core component is 15-25:85-75; it overcomes the disadvantages of PEN polyester being difficult to fiberize and not easy to dye, and enables the fiber to maintain the unique chemical stability, gas barrier, flame retardancy and heat resistance of PEN polyester fiber; the invention organically combines the economy of PET polyester with the excellent properties of PEN polyester fiber, greatly reduces the use cost of PEN polyester, will expand the application of PEN polyester in the fiber field, and at the same time can further expand the use of PET polyester fiber in the industrial field.

[0006] It can be seen from the above disclosed technologies that the skin layer is gradually developed into polyester materials based on the polyolefin materials, so as to achieve improvements in mechanical properties, flame retardancy and other properties.

[0007] Chinese invention patent CN116988186A discloses a biodegradable low-melting-point sheath-core composite fiber and a preparation method thereof, wherein the composite fiber is a sheath layer of polylactic acid-based polyurethane with different hard segment molecular weights and a core layer of polylactic acid; the sheath layer includes a soft segment and a hard segment, the soft segment is polylactic acid diol, and the hard segment molecular weights are different. Chinese invention patent CN117026418A relates to a fully biodegradable sheath-core composite fiber and a preparation method thereof, wherein the preparation method is: using a biodegradable polyester mixed with thermoplastic starch as a sheath raw material, and polylactic acid as a core raw material, and according to a sheath-core composite spinning process, a fully biodegradable sheath-core composite fiber is prepared; the product: the sheath layer is a biodegradable polyester, the biodegradable polyester is mixed with thermoplastic starch, and the core layer is polylactic acid; the content of thermoplastic starch in the biodegradable polyester does not exceed 2wt%. The invention uses a biodegradable polyester with excellent softness as the sheath layer and polylactic acid as the core layer, giving full play to the low melting point adhesion of the sheath layer component and the skeleton support of the core layer, and introducing thermoplastic starch into the sheath layer promotes the crystallization properties of the biodegradable polyester in the sheath layer and improves the processability. The fully biodegradable sheath-core composite fiber spun by this invention is skin-friendly and soft, has good hot air adhesion, and achieves the unity of application performance and biodegradability.

[0008] The above patents further combine biodegradable polyester materials with skin-core composites to meet the requirements of hot air processing, and at the same time, the prepared products have biodegradable properties.

[0009] ES fiber is a representative variety of core-skin composite fiber and is the main raw material for disposable sanitary products such as sanitary napkins, diapers, and panty liners. In recent years, the demand for raw ES fiber has gradually increased. With the expansion of application areas and the continuous improvement of downstream performance, it is suitable for the production of sanitary materials, thermal insulation filling materials, filter materials and other products using hot air penetration technology. New requirements are constantly being put forward for core-skin composite fibers, such as mechanical strength and compressive resilience under repeated external compression forces. In essence, new requirements are put forward for the raw materials of core-skin composite fibers. Summary of the invention

[0010] The present invention aims to solve the problems of thermodynamic incompatibility between the skin and core layers of existing ES fibers, easy cracking, insufficient mechanical strength and insufficient compression resilience when used as thermal insulation filling materials, and provides a high-compression resilience skin-core composite fiber and a preparation method thereof. The skin and core layers can be stretched and oriented synchronously, and the interface bonding strength is higher, which solves the fiber cracking problem and improves the strength of the composite fiber. The skin and core layers have a regular sequence structure and certain crystallization properties, which also ensures that no bonding problems occur during drying before composite spinning. The skin layer is a low-viscosity polyester and the core layer is a high-viscosity polyester. At the same time, the skin layer and the core layer have their own elastic characteristics, realizing the rebound of two mechanisms: the elasticity of the polymer itself and the curling recovery of the composite fiber, and significantly improving the compression resilience performance of the composite fiber.

[0011] The method for preparing a high-compression-rebound sheath-core composite fiber comprises the following steps: preparing a copolyester A with three chain segment structures by a step-by-step esterification method and a cocondensation method as a sheath layer; preparing a copolyester B with two chain segment structures by a coesterification and cocondensation method as a core layer; and preparing a composite fiber with excellent compression rebound rate through sheath-core composite spinning.

[0012] As the preferred technical solution:

[0013] As described above, a high compression and resilience sheath-core composite fiber and a preparation method thereof, the specific steps are as follows:

[0014] A method for preparing a high-compression and resilient sheath-core composite fiber as described above, wherein the sheath copolyester is prepared by a step-by-step esterification method and a co-condensation method, and contains three segment structures, and specifically, one of the segment A1 components is prepared by a step-by-step esterification method, which is an esterification reaction of terephthalic acid with 1,5-pentanediol or 1,6-hexanediol, the molar ratio of acid to alcohol is 1:1.1-1.6, the esterification reaction temperature is 215-240°C, the esterification time is 2-3.5h, and the esterification pressure is 0.1-0.25MPa;

[0015] A method for preparing a high-compression and resilient sheath-core composite fiber as described above, wherein the sheath copolyester A2 segment is produced by esterification reaction of adipic acid with butanediol, 1,5-pentanediol or 1,6-hexanediol, the molar ratio of acid to alcohol is 1:1.2-1.8, the esterification reaction temperature is 200-220°C, the esterification time is 2.5-3.5h, and the esterification pressure is 0.10-0.20MPa;

[0016] A method for preparing a high-compression and resilient sheath-core composite fiber as described above, wherein the sheath copolyester is prepared by co-condensing the esterification products A1 and A2 with polyethylene glycol at a co-condensation temperature of 240-275°C, a pressure of less than 100 Pa, and a time of 2.0-4.0 hours;

[0017] A method for preparing a high compression and resilience sheath-core composite fiber as described above, wherein the mixed mass fraction of A1 and A2 is 20:80-80:20, and the amount of polyethylene glycol added is 5-15% of the sum of the mass of A1 and A2;

[0018] A method for preparing a high compression and resilience sheath-core composite fiber as described above, wherein the number average molecular weight of the polyethylene glycol is 1500-4000 g / mol;

[0019] According to the method for preparing a high-compression and resilient sheath-core composite fiber, the copolyester prepared by co-condensation of A1, A2 and polyethylene glycol has an intrinsic viscosity of 0.55-0.65 dL / g and a melt index of 20-30 g / 10 min;

[0020] In the above-mentioned method for preparing a high-compression and resilient sheath-core composite fiber, the core layer B is prepared by a co-esterification and co-polycondensation method, specifically, terephthalic acid, ethylene glycol, butanediol or propylene glycol are co-esterified with polyethylene glycol, and then co-polycondensed. The co-esterification reaction temperature is 220-245°C, the reaction time is 3.0-4.5h, and the esterification pressure is 0.1-0.35MPa; the co-polycondensation reaction temperature is 250-280°C, the reaction time is 2.0-4.0h, and the pressure is within 100Pa;

[0021] In the method for preparing a high compression and resilience sheath-core composite fiber as described above, one of the terephthalic acid, ethylene glycol, butanediol or propylene glycol is co-esterified with polyethylene glycol, and the molar ratio of the three substances is 1:1.2-1.5:0.01-0.10. The number average molecular weight of polyethylene glycol is 600-1000 g / mol;

[0022] A method for preparing a high compression and resilience sheath-core composite fiber as described above, wherein the core layer B has an intrinsic viscosity of 0.80-1.20 dL / g and a melt index of 20-30 g / 10 min;

[0023] According to the above-mentioned method for preparing a high-compression and resilience sheath-core composite fiber, the synthesized sheath layer A and the core layer B are composite-spun, wherein the mass ratio of A to B is 2:8-5:5, the single-filament fineness of the composite fiber is 1.0-3.0 dtex, the mechanical strength is ≥2.5 cN / dtex, and the compression resilience is ≥85%.

[0024] Principle of the Invention

[0025] The traditional ES fiber skin is a low melting point polymer, i.e., polyolefin, and the core layer is mostly PET polyester. It is prepared by two-component skin-core composite spinning. The low melting point characteristics of the skin polyolefin are used to realize the bonding of the fiber skin layer into a net under the hot air process and then make specific products, which has the advantages of being fluffy and breathable. However, the skin-core polyolefin and the core polyester are two types of polymers, and the thermodynamic properties are quite different, which makes it difficult for the skin and the core to achieve synchronous stretching during the spinning process, showing that the strength of the composite fiber is limited, and there are problems such as cracking. In addition, ES fiber has a certain degree of fluffiness, but under conditions such as compression, the fiber mainly relies on the fiber curling morphology to achieve rebound, and the rebound performance is very limited, resulting in its use in filling products. The present invention is aimed at the shortcomings of ES fiber. The skin and the core are both composited with polyester polymers. The chemical structure of the skin and the core is similar, and the thermodynamic compatibility is better. Under the tensile force of the composite fiber, the skin and the core can achieve synchronous stretching and orientation, and the interface bonding strength is higher, which solves the fiber cracking problem and improves the strength of the composite fiber.

[0026] The sheath-core two-component composite fiber, the sheath as one of the components, plays the role of hot air bonding in post-processing, and the core acts as a rigid skeleton. In order to improve the rebound under external compression force, the molecular weight of the core layer polyester is often increased in the sheath-core composite fiber, but the increase in molecular weight will cause its fluidity to decrease, resulting in the mismatch between the fluidity of the core layer and the sheath of the composite fiber, affecting the processing continuity. In addition, although the compression resilience can be improved to a certain extent by increasing the molecular weight of the core layer polyester, the overall modulus of the composite fiber is enhanced, showing a decrease in softness, which affects the skin affinity of the composite fiber. The core layer of the present invention is a copolyester prepared by co-esterification of one of terephthalic acid, ethylene glycol or butanediol or propylene glycol with polyethylene glycol, and then co-condensation reaction, which has both high molecular weight and high flow properties. The copolyester contains two segment structures, namely, the hard end formed by terephthalic acid, ethylene glycol or butanediol or propylene glycol, and the soft segment formed by polyethylene glycol. The combination of the soft segment and the hard segment in the copolyester presents an "elastomer" feature. The hard segment ensures the basic rigidity, and the soft segment promotes the fluidity of the copolyester. Terephthalic acid, ethylene glycol, butanediol or propylene glycol are co-esterified with polyethylene glycol, and the molar ratio of the three substances is 1:1.2-1.5:0.01-0.10. The number average molecular weight of polyethylene glycol is 600-1000g / mol. The copolyester with two chain segment structures has crystalline properties, ensuring that no adhesion occurs during drying before composite spinning. Co-esterification can achieve full reaction of the relatively low molecular weight polyethylene glycol introduced, preventing it from being drawn out of the system by negative pressure during the polycondensation stage.

[0027] The step-by-step esterification method and the co-condensation method are used to prepare copolyesters with three segment structures as the cortex. The two types of polyesters are first esterified to form esters, that is, the corresponding segments are then co-condensed with polyethylene glycol with a relatively high molecular weight to prepare copolyesters with three segment structures. The segment structure in the copolyester can be regulated by the addition amount of the three components. The segments formed by the distributed esterification can achieve a regular sequence structure of the prepared copolyester with certain crystallization properties, and also ensure that it does not stick during drying before composite spinning.

[0028] The synthesized skin copolyester with three chain segment structures and the core copolyester with two chain segment structures are composite spun. The soft segment and hard segment in the skin and core copolyesters have different response times to temperature and stress, and both have elastomeric characteristics. After the skin and core are composited, the skin is a low-viscosity polyester and the core is a high-viscosity polyester. The viscosity difference will give the composite fiber a self-curling structure. The curling structure has the characteristics of fluffy and rebound. At the same time, the elastic characteristics of the skin and core layers themselves realize the rebound of the two mechanisms of polymer elasticity and composite fiber curling recovery, which significantly improves the compression rebound performance of the composite fiber.

[0029] Beneficial Effects

[0030] (1) The present invention addresses the deficiencies of ES fibers. The skin layer and the core layer are compounded with polyester polymers. The chemical structures of the two components of the skin and the core are similar, and the thermodynamic compatibility is better. Under the tensile force of the composite fiber, the skin layer and the core layer can be stretched and oriented synchronously, and the interface bonding strength is higher, which solves the problem of fiber cracking and improves the strength of the composite fiber.

[0031] (2) The copolyester of the skin layer and the core layer of the present invention can regulate its segment composition during the synthesis stage, and has a regular sequence structure and certain crystallization properties, which also ensures that no bonding problem occurs during drying before composite spinning.

[0032] (3) The sheath-core composite fiber of the present invention has a sheath layer of low-viscosity polyester and a core layer of high-viscosity polyester. The viscosity difference will give the composite fiber a self-curling structure, and the curled structure has the characteristics of fluffy and resilient. At the same time, the elastic characteristics of the sheath and the core layer themselves realize the rebound of two mechanisms: the elasticity of the polymer itself and the curling recovery of the composite fiber, which significantly improves the compression rebound performance of the composite fiber. DETAILED DESCRIPTION

[0033] Embodiment 1-9:

[0034] Referring to Table 1, terephthalic acid and different alcohols (1,5-pentanediol or 1,6-hexanediol) are subjected to esterification reaction at different molar ratios to generate esterification product A1, the esterification reaction temperature is 215-240° C., the esterification time is 2-3.5 h, and the esterification pressure is 0.10-0.25 MPa.

[0035] Adipic acid is subjected to esterification reaction with different alcohols (butanediol, 1,5-pentanediol or 1,6-hexanediol) in different molar ratios to generate esterification product A2, the esterification reaction temperature is 200-220° C., the esterification time is 2.5-3.5 h, and the esterification pressure is 0.10-0.20 MPa.

[0036] The esterification products A1 and A2 with different mass fractions are co-condensed with polyethylene glycol, the number average molecular weight of polyethylene glycol is 1500-4000 g / mol, the co-condensation temperature is 240-255°C or 255°C-275°C, the pressure is within 100 Pa, and the time is 2.0-4.0 h to prepare the copolyester A in Examples 1-9. The intrinsic viscosity of copolyester A is 0.55-0.65 dL / g, the melt index is 20-30 g / 10min, and the melting point is 125-140°C.

[0037] Referring to Table 2, terephthalic acid, different alcohols (ethylene glycol, butanediol or propylene glycol) and polyethylene glycol are co-esterified according to different molar ratios in Table 2, and then co-polycondensed to obtain copolyester B in Examples 1-9. The number average molecular weight of polyethylene glycol is 600-1000 g / mol. The co-esterification reaction temperature is 220-245°C, the reaction time is 3.0-4.5h, and the esterification pressure is 0.1-0.35MPa; the co-polycondensation reaction temperature is 250-280°C, the reaction time is 2.0-4.0h, and the pressure is within 100Pa. The intrinsic viscosity of copolyester B is 0.80-1.20dL / g, and the melt index is 20-30g / 10min.

[0038] As shown in Table 2, the skin layer copolyester A and the core layer copolyester B are spun together at different mass ratios according to conventional processes to obtain composite fibers. The single fiber fineness of the composite fiber is 1.0-3.0 dtex, the mechanical strength is ≥2.5 cN / dtex, and the compression rebound rate is ≥85%. The test standard for the compression rebound rate is "FZ / T 52010-2014 Regenerated Polyester Staple Fiber Appendix A Compression Elastic Recovery Rate Test Method".

[0039] The present invention provides a high compression rebound sheath-core composite fiber and a preparation method thereof, which involves synthesizing a new type of copolyester and then using a sheath-core composite spinning method to prepare a composite fiber with excellent compression rebound rate. A step-by-step esterification method and a co-polycondensation method are used to prepare a copolyester A with three chain segment structures as the sheath layer, and the melting point is 125-140°C; a copolyester B with two chain segment structures is prepared by a co-esterification and co-polycondensation method as the core layer, and the core layer and the sheath layer have equivalent fluidity at the same temperature, and the melt index is 20-30g / 10min. After the sheath-core composite spinning, a composite fiber with excellent compression rebound rate is prepared, and the fiber mechanical strength is ≥2.5cN / dtex, the compression rebound rate is ≥85%, it is soft, skin-friendly and comfortable, and anti-cracking. It can meet the requirements of hot air process molding and processing, and is widely used in diapers, sanitary napkins and other products.

[0040] Table 1:

[0041]

[0042] Table 2:

[0043]

Claims

1. A method for preparing a high compression and resilience sheath-core composite fiber, characterized in that: A copolyester A with three chain segment structures is prepared by a step-by-step esterification method and a co-condensation method as a skin layer, and the melting point is 125-140°C; a copolyester B with two chain segment structures is prepared by a co-esterification and co-condensation method as a core layer, and the core layer and the skin layer have the same fluidity at the same temperature, and the melt index is 20-30g / 10min. A high compression and resilience skin-core composite fiber is obtained by skin-core composite spinning; The stepwise esterification method and the co-condensation method are used to prepare the copolyester A of three chain segment structures as the skin layer. The stepwise esterification is to esterify terephthalic acid with 1,5-pentanediol or 1,6-hexanediol to generate the esterification product A1, the molar ratio of acid to alcohol is 1:1.1-1.6, the esterification reaction temperature is 215-240°C, the esterification time is 2-3.5h, and the esterification pressure is 0.1-0.25MPa; the ... molar ratio of acid to alcohol is 1:1.1-1.6, the molar ratio of acid to alcohol is 1:1.1-1.6, the molar ratio of acid to alcohol is 1:1 6-hexanediol is subjected to an esterification reaction to generate an esterification product A2, wherein the molar ratio of acid to alcohol is 1:1.2-1.8, the esterification reaction temperature is 200-220° C., the esterification time is 2.5-3.5 h, and the esterification pressure is 0.10-0.20 MPa; the esterification product A1, the esterification product A2 and polyethylene glycol are subjected to co-condensation reaction at a co-condensation temperature of 240-275° C., a pressure of less than 100 Pa, and a time of 2.0-4.0 h to prepare a copolyester A; The copolyester B with two chain segment structures is prepared as the core layer by the method of co-esterification and co-polycondensation, wherein terephthalic acid, ethylene glycol, butanediol or propylene glycol are co-esterified with polyethylene glycol, and then co-polycondensed; the co-esterification reaction temperature is 220-245°C, the reaction time is 3.0-4.5h, and the esterification pressure is 0.1-0.35MPa; the co-polycondensation reaction temperature is 250-280°C, the reaction time is 2.0-4.0h, and the pressure is within 100Pa.

2. The method for preparing a high compression and resilience sheath-core composite fiber according to claim 1, characterized in that: The esterification product A1, the esterification product A2 and the polyethylene glycol are then co-condensed, the mixed mass fraction of the esterification product A1 and the esterification product A2 is 20:80-80:20, the amount of polyethylene glycol added is 5-15% of the sum of the masses of the esterification product A1 and the esterification product A2, and the number average molecular weight of the polyethylene glycol is 1500-4000 g / mol.

3. The method for preparing a high compression and resilience sheath-core composite fiber according to claim 2, characterized in that: The intrinsic viscosity of copolyester A is 0.55-0.65 dL / g, and the melt index is 20-30 g / 10 min.

4. The method for preparing a high compression and resilience sheath-core composite fiber according to claim 1, characterized in that: Terephthalic acid, ethylene glycol, butanediol or propylene glycol are co-esterified with polyethylene glycol, and the molar ratio of the three substances is 1:1.2-1.5:0.01-0.10; the number average molecular weight of polyethylene glycol is 600-1000 g / mol.

5. The method for preparing a high compression and resilience sheath-core composite fiber according to claim 4, characterized in that: The intrinsic viscosity of copolyester B is 0.80-1.20 dL / g, and the melt index is 20-30 g / 10min.

6. The method for preparing a high compression and resilience sheath-core composite fiber according to claim 1, characterized in that: The copolyester A is used as the skin layer and the copolyester B is used as the core layer for composite spinning, wherein the mass ratio of the copolyester A to the copolyester B is 2:8-5:

5.

7. A high-compression-resilience sheath-core composite fiber prepared by the method for preparing a high-compression-resilience sheath-core composite fiber according to any one of claims 1 to 6, characterized in that: The single fiber fineness of the composite fiber is 1.0-3.0 dtex, the mechanical strength is ≥2.5 cN / dtex, and the compression rebound rate is ≥85%.

Citation Information

Patent Citations

  • Colored polyester concentric sheath-core composite fiber and manufacturing method thereof

    CN104532399A

  • Antibacterial ES fiber for cool-feeling non-woven fabric and preparation method of antibacterial ES fiber

    CN114875518A

  • Elastic ES fiber with three-dimensional spiral structure and preparation method of elastic ES fiber

    CN116695280A

  • Biodegradable low-melting-point sheath-core composite fiber and preparation method thereof

    CN116988186A

  • Fully biodegradable sheath-core composite fiber and preparation method thereof

    CN117026418A